Aglomerações produtivas nos setores de atividade econômica do Ceará: análise temporal e espacial - Nagaki, Marcos Antonio Feijó (2017)
The objective of this work is to identify and analyze the dynamics of the spatial distribution of the sectors of economic activity foreseen in the determination of the Gross Domestic Product (GDP) - Agriculture, Industry and Services, and of the sub-sectors of Public Administration and Commerce in the state of Ceara for the period 2002-2014. Therefore, we will investigate the evolution of clusters, as well as the spatial relationship between the stock concentration of formal jobs and the Gross Value Added (GVA) of these sectors. For this purpose, was used the method of Exploratory Analysis of Spatial Data (AEDE) applied to the sectorial concentration, which was measured by means of the Normalized Concentration Index (ICn).